The Expanding universe of sculpture - Hartley, Irving; Hartley, Elda. ([S.l.] Hartley Productions, 1970)
Takes a look at the studies of some of the Osutanding sculptors of today--Reubian Nakain, Alex Lieberman, David Burt, Doris Chase. Includes interviews with them about their works and their philosohy that motivates them. Shows their oustanding collections and the varsity of materials they used.
VHS.
Keywords: Sculpture -- Exhibition